2005
DOI: 10.1136/bjo.2004.049296
|View full text |Cite
|
Sign up to set email alerts
|

The origins of polypoidal choroidal vasculopathy

Abstract: Background/aim: There are two theories on the pathogenesis of polypoidal choroidal vasculopathy (PCV): variants in choroidal neovascularisation (CNV) and inner choroidal vessel abnormalities. On indocyanine green angiography (IGA) with a video camera system, PCV has a characteristic appearance, but inadequate image quality has made detailed interpretation difficult. This study aims to improve imaging, using confocal scanning laser ophthalmoscopy (SLO), to elucidate the pathogenesis of PCV. Methods: High speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 26 publications
8
159
3
Order By: Relevance
“…It was based on disease characteristics of elevated orange-red lesions (not resembling a PED, choroidal hemangioma, or subretinal blood) on clinical examination or characteristic polypoidal vasculature on ICGA. 9 Exclusion criteria included previous history of AMD, history of PDT, a high myopia (of 46 D) and pre-existing macular scar.…”
Section: Methodsmentioning
confidence: 99%
“…It was based on disease characteristics of elevated orange-red lesions (not resembling a PED, choroidal hemangioma, or subretinal blood) on clinical examination or characteristic polypoidal vasculature on ICGA. 9 Exclusion criteria included previous history of AMD, history of PDT, a high myopia (of 46 D) and pre-existing macular scar.…”
Section: Methodsmentioning
confidence: 99%
“…In ICGA, PCV is typically characterized by distinct forms of choroidal vascular abnormalities, including characteristic polypoidal lesions with or without branching vascular networks (BVNs) of choroidal origin [50]. As described above, polyp lesions are mostly present at the margin and inside the PED, which may cause a ‘notch sign' between the PED, including polyp lesions and connecting PED, which includes the BVN.…”
Section: Angiographic Imagingmentioning
confidence: 99%
“…Studying CSLO-ICGA, Yuzawa et al 39 observed that in some cases the BVN showed pulsatile flow, suggesting that they emanate from inner choroidal arterioles. The authors concluded that there may be two types of BVN, one represents intra-choroidal vascular abnormality ('PCV in the narrow sense'), the other represents neovascularization ('polypoidal CNV') that grows rapidly in the sub-RPE space.…”
mentioning
confidence: 99%